PROFIL MATCHING : SUATU PENDEKATAN PADA PROSES PENGAMBILAN KEPUTUSAN UNTUK KELAYAKAN PEMBERIAN KREDIT SEPEDA MOTOR - Reny Wahyuning Astuti; Hambali Furnawan; Marulak Panjaitan (JURNAL AKADEMIKA)
In the business world, especially the second motorcycle loans, the analysis resultsvery risky and harmful because it can lead to the emergence of wanpretasi or bad credit due to credit payments are not current. Departing from these problems then made a software which aims to analyze the weight of a prospective consumer credit competence so that the results are more accurate due to the use of computer logic and calculation results more certain marginal value of the error is smaller. The method digunakaan in credit analysis is the method of profile matching . This method is a decision-making mechanism by assuming that there is an ideal level of predictor variables that must be met by the subject under study and not the minimum level that must be met or passed.In addition to the software which serves as a decision support system, the author also includes a data processing application motorcycle loan transaction so that the intended use of the software more leverage.